2007
DOI: 10.1111/j.1463-5224.2007.00536.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the clinical efficacy of subconjunctival injection of clindamycin in the treatment of naturally occurring infectious bovine keratoconjunctivitis

Abstract: The results of this study suggest that subconjunctival injection of clindamycin is effective in the treatment of naturally occurring infectious bovine keratoconjunctivitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Along with oxytetracycline, tulathromycin, florfenicol, and ceftiofur, clindamycin, 16 tilmicosin, 19 ormetoprim-sulfadimethoxine (related to trimethoprim-sulfamethoxazole), 18 and penicillin [1][2][3] have been shown to be effective in treating IBK associated with M. bovis. Of these antibiotics, M. bovoculi had the highest percent resistance to penicillin (12.3%); whether or The relatively low MIC values reported for M. bovoculi in the present study support the conclusion that commonly used antibiotics against M. bovis should also be effective against M. bovoculi.…”
mentioning
confidence: 99%
“…Along with oxytetracycline, tulathromycin, florfenicol, and ceftiofur, clindamycin, 16 tilmicosin, 19 ormetoprim-sulfadimethoxine (related to trimethoprim-sulfamethoxazole), 18 and penicillin [1][2][3] have been shown to be effective in treating IBK associated with M. bovis. Of these antibiotics, M. bovoculi had the highest percent resistance to penicillin (12.3%); whether or The relatively low MIC values reported for M. bovoculi in the present study support the conclusion that commonly used antibiotics against M. bovis should also be effective against M. bovoculi.…”
mentioning
confidence: 99%
“…This route may also establish a greater intraocular concentration of corticosteroids than is possible using frequent topical applications, 21 facilitating the management of ophthalmic diseases in livestock animals. 22 In spite of it, atropine eye drops proved to produce a longerlasting effect of 13 h and to promote a more pronounced pupillary dilation (0.9 mm) when compared with the same drug delivered through the subconjunctival route. Studies in dogs demonstrated that subconjunctival route was less efficient in stabilizing blood-aqueous barrier than the topical route after the use of anti-inflammatory drugs.…”
Section: Discussionmentioning
confidence: 98%
“…One major advantage attributed to subconjunctival drug administration is the reduced need for frequent topical application. This route may also establish a greater intraocular concentration of corticosteroids than is possible using frequent topical applications, facilitating the management of ophthalmic diseases in livestock animals . In spite of it, atropine eye drops proved to produce a longer‐lasting effect of 13 h and to promote a more pronounced pupillary dilation (0.9 mm) when compared with the same drug delivered through the subconjunctival route.…”
Section: Discussionmentioning
confidence: 99%
“…A Spanish language trial could not be extracted because the authors did not report the number of calves allocated per treatment arm (Abdala et al, 2002). Thus from the 17 manuscripts, 13 contained data suitable for extraction (George et al, 1988(George et al, , 1989Chadli, 1992;Allen et al, 1995;Eastman et al, 1998;Angelos et al, 2000;Gokce et al, 2002;Zielinski et al, 2002;Dueger et al, 2004;Starke et al, 2007;Senturk et al, 2007;Freedom of Information Summary, 2007;Quesada et al, 2010).Author definitions of the outcomes are included in the supplemental material. Table 2 and Table 3 provide the population and study characteristics of each manuscript for which data were extracted.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Table 2 and Table 3 provide the population and study characteristics of each manuscript for which data were extracted. Since the original systematic review in 2006, four new randomized trials have been published (Starke et al, 2007;Senturk et al, 2007;Freedom of Information Summary, 2007;Quesada et al, 2010). One of the four trials was only available in French (Senturk et al, 2007) and one was an FDA drug application (Freedom of Information Summary, 2007).…”
Section: Study Characteristicsmentioning
confidence: 99%